Workload, Employee Engagement, and Turnover Intention Among Contract Workers in Seafood Processing Industry - Riska Veronika; Farah Chalida Hanoum T; Shofif Sobaruddin Akbar (Al-Qalam Institue, 2026)
This study aims to examine the effects of workload and employee engagement on turnover intention among contract employees and to explain their contribution to employees’ intention to leave the organization. A quantitative explanatory research design was employed using a survey approach. Data were collected through an online questionnaire from 100 respondents selected using simple random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS, including measurement model evaluation, structural model assessment, and bootstrapping for hypothesis testing. The results indicate that workload has a positive and significant effect on turnover intention, suggesting that excessive job demands increase employees’ intention to leave the organization. Unexpectedly, employee engagement also shows a positive and significant effect on turnover intention, indicating that among contract employees, high engagement may reflect commitment to work responsibilities rather than long-term organizational attachment. Furthermore, workload and employee engagement jointly explain a substantial proportion of the variance in turnover intention. These findings extend the application of the Job Demands–Resources perspective by demonstrating that employee engagement does not necessarily function as a retention mechanism under contractual employment conditions. Practically, organizations should balance workload while strengthening employment security and career development policies to reduce turnover intention.